Toward an Epistemology of Practice - Joseph A. Raelin (Academy of Management Learning & Education, 2007)
Higher and post-experience education in many parts of the world has unfortunately overlooked what practice can contribute to our knowledge base distinctly and additively from classroom education. Ultimately, we need a synthesis of theory and practice if we are to prepare thoughtful practitioners. Using conceptual and practical approaches from constructionist thought borrowing such tools as tacit knowledge, critical reflection, and mastery, this paper proposes a means to effect such a synthesis. Needed is a new epistemology of practice that adds praxis to classroom education in order to help learners deconstruct the structures and systems that embed their social environments. The paper also examines the outcomes and particular competencies that emanate from a practice-based learning. Implications for teaching by learning from this practice epistemology are discussed.
Keywords: M53; M51; M10; I21; J24; O31; 650; Epistemology; Theory and practice; Reflective practice; Social constructionism; Critical theory; Expertise; Tacit knowledge; Practice-based learning; Local knowledge; Postmodernism